Steganografi Penyisipan Pesan Pada File Citra Dengan Menggunakan Metode LSB (Least Significant Bit) - Buha Johannes Simbolon (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
The rapid development of technology not only has a positive impact, but can also have a negative impact on the users of this technology. One of them is the development of cyber crime which causes messages to be unsafe to protect. Message security can be protected by using steganography to convert messages into secret passwords. To make the secret password more secure, steganography techniques are used. Steganography is a technique for hiding messages by inserting messages into other containers. In this study, a combination of two algorithms is used, namely the RC4 and Base Cryptography algorithm, which is better known as the Super Encryption algorithm and the steganography technique using the Least Significant Bit (LSB) method with random pixel insertion using a pseudorandom number generator (PRNG). Algorithm use. the scope of the problem is the information insertion media used, the process of making data into information and sending to message recipients, the method used in writing the thesis using LSB (Least Significant Bit) and the programming language used in building this system is PHP (Hypertext Preprocessor) with MySQL database (My Structured Query Language) on PhpMyAdmin.